2018
DOI: 10.1111/bjop.12336
|View full text |Cite
|
Sign up to set email alerts
|

Against all odds – is a more differentiated view of personality development in emerging adulthood needed? The case of young apprentices

Abstract: Personality development in emerging adults who do not attend college after high school has been largely overlooked so far. In this study, we investigated personality development in emerging German adults (N = 1,886, M = 18.01 years, 29% female) undergoing vocational education and training (VET). The trainees were assessed at the start of VET, 1.5 years later, and another 1.5 years after that, just before graduation. Longitudinal latent change score analyses were applied. Bivariate analyses investigated life sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 85 publications
(155 reference statements)
1
11
1
Order By: Relevance
“…Contrary to previous studies, the emerging adults working at their first job decreased in all of the Big Five personality traits and, thus, they did not develop according to the maturity principle in the first 1.5 years of their first job experience (Deventer et al, 2019). This is a surprising finding because the context of a person's first job has been associated with development toward more emotional stability, agreeableness, and conscientiousness (e.g., Lodi-Smith & Roberts, 2007;Specht et al, 2011).…”
Section: Personality Development and Bpn Support-different Trait Difcontrasting
confidence: 83%
See 3 more Smart Citations
“…Contrary to previous studies, the emerging adults working at their first job decreased in all of the Big Five personality traits and, thus, they did not develop according to the maturity principle in the first 1.5 years of their first job experience (Deventer et al, 2019). This is a surprising finding because the context of a person's first job has been associated with development toward more emotional stability, agreeableness, and conscientiousness (e.g., Lodi-Smith & Roberts, 2007;Specht et al, 2011).…”
Section: Personality Development and Bpn Support-different Trait Difcontrasting
confidence: 83%
“…That is, the emerging adults reported that they had become less emotionally stable (d = -0.34), less extraverted (d = -0.30), less open (d = -0.09), less agreeable (d = -0.41), and less conscientious (d = -0.49) on average. Personality consistency was moderate with values of r = .50 for emotional stability, r = .65 for extraversion, r = .58 for openness and agreeableness, and r = .57 for conscientiousness, indicating that extraversion was most and emotional stability least stable which has been shown in a previous study on mean-level personality change and individual differences in change with this sample (Deventer, Lüdtke, Nagy, Retelsdorf, & Wagner, 2019). With respect to initial correlations, the importance of BPN support was more strongly related to perceived BPN support (autonomy: r = .38; competence: r = .41; relatedness: r = .48) than the personality traits were to either BPN support (.15 < r < .30) or importance of BPN support (.13 < r < .30).…”
Section: Analysessupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, work and career investments can lead to increases in agreeableness and conscientiousness (Hudson & Roberts, 2016). However, the evidence is less robust regarding several other work-related factors such as the transition into the first job (Deventer et al, 2019) or retirement (Schwaba & Bleidorn, 2018). Even less is known about conditions of developmental paths within the working context such as transactional processes between work-role demands and personality change across the adult lifespan (Denissen et al, 2013).…”
Section: What Do We Know?mentioning
confidence: 99%